Automatic detection of pitching and throwing events in baseball with inertial measurement sensors - Murray, N. B.; Black, G. M.; Whiteley, R. J.; Gahan, P.; Cole, M. H.; Utting, A.; Gabbett, T. J. (International Journal of Sports Physiology and Performance, 2017)
Purpose: Throwing loads are known to be closely related to injury risk. However, for logistic reasons, typically only pitchers have their throws counted, and then only during innings. Accordingly, all other throws made are not counted, so estimates of throws made by players may be inaccurately recorded and underreported. A potential solution to this is the use of wearable microtechnology to automatically detect, quantify, and report pitch counts in baseball. This study investigated the accuracy of detection of baseball pitching and throwing in both practice and competition using a commercially available wearable microtechnology unit.